Cultural logics of honor, face, and dignity as moderators of the relationship between group process and pro-migrant collective action intentions - Tomasz Besta; Emma Thomas; Goksu Celikkol; Michał Olech; Paweł Jurek; Martijn van Zomeren; Maura Pozzi; Carlo Pistoni; Marek Palace; Gulcin Akbas; Julia C. Becker; Maja Becker; et al. (Current Research in Ecological and Social Psychology)
Although group identification, efficacy, and injustice appraisals are well-established predictors of collective action support, contextual factors are rarely examined. We address this oversight in preregistered study by testing whether country-level norms moderate the relationships identity, anger at injustice, and efficacy have with support for pro-immigrant solidarity collective action using data from 22 countries (N = 4615). Given that cultures that emphasize honor and face prioritize harmony and social cohesion over conflict, we expected that honor codes and face orientation would attenuate the links identity, injustice, and efficacy have with collective action support. Results showed that identification, efficacy, and anger at injustice were linked to collective action intentions in most countries, but honor codes attenuated the relationship between anger and collective action intentions. We further discuss the implications and limitations of these results in light of cross-cultural studies of pro-immigrant attitudes and actions. Overall, our findings complement research on predictors of collective action and the dual-chamber model of collective action by presenting potential cultural constraints.